2020
DOI: 10.1088/1748-0221/15/06/p06008
|View full text |Cite
|
Sign up to set email alerts
|

A beta-gamma position-sensitive detector based on rod plastic scintillators and artificial neural networks

Abstract: Mixed fields of gamma and beta radiations may exist under different conditions such as radiation dosimetry, PET medical imaging, medical therapy treatments, space radiation detection, etc. In these circumstances, it is important to determine the dose rate, intensity, incident position of the beta particles and gamma radiation separately. In this work, a radiation detector was developed, which could monitor the incident position and type of beta particles and gamma rays in the mixed radiation fields. The detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For conventional analog SiPM arrays, typical position sensing may require a large number of readout channels and may show limited position resolution due to the SiPM's pixel size [208]. To achieve higher spatial resolution, artificial neural networks [131,209] and novel position-sensitive SiPM (PS-SiPM) fabrication processes [210,211] can increase the position sensing performance. Multiplexing [25,212] and multi-channel integrated readouts [164,213,214] simplify the readout and improve performance characteristics (Figure 15).…”
Section: Position Sensingmentioning
confidence: 99%
“…For conventional analog SiPM arrays, typical position sensing may require a large number of readout channels and may show limited position resolution due to the SiPM's pixel size [208]. To achieve higher spatial resolution, artificial neural networks [131,209] and novel position-sensitive SiPM (PS-SiPM) fabrication processes [210,211] can increase the position sensing performance. Multiplexing [25,212] and multi-channel integrated readouts [164,213,214] simplify the readout and improve performance characteristics (Figure 15).…”
Section: Position Sensingmentioning
confidence: 99%
“…One type of the detectors that can be employed in such tomography systems are high aspect ratio scintillators. The possibility of detecting the incident position of gamma-rays with scintillation rod detectors has already been studied and investigated [7][8][9][10]. This ability of the rod scintillators makes them as a candidate for employing in gamma/x-ray industrial computed tomography systems suitable for large objects.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this type of scintillator is inherently positionsensitive and can be employed as linear detectors for gamma/x-ray imaging and tomography purposes. In the proposed system, we used inorganic scintillators (such as NaI(Tl) or CsI(Na)) instead of organic scintillators (such as plastic or liquid scintillators) because the organic scintillators have a low atomic number and therefore their absorption efficiency is lower than the inorganic scintillators [24]- [27]. Furthermore, due to their small photoelectric cross-section, these scintillators do not show photopeak in their spectral response.…”
Section: Introductionmentioning
confidence: 99%